Optimized sowing time combined with targeted insecticide application enhances faba bean (Vicia faba L.) yield by suppressing Bruchus rufimanus damage in Lithuania - Almogdad, Mohammad; Semaškienė, Roma; Jonavičienė, Akvilė; Ramanauskienė, Jūratė; Venslovas, Eimantas; Sabeckis, Aurimas; Lavrukaitė, Karolina; Alkuddsi, Yanal; Almukdad, Manal (Frontiers in Agronomy, 2025)
A field experiment was conducted in Lithuania over three growing seasons (2021–2023) to evaluate the effects of sowing time, seeding rate, and insecticide application on grain damage caused by Bruchus rufimanus, as well as on grain yield and quality. The experiment included both insecticide-treated and untreated plots, along with three seeding rates and three sowing times. Early sowing resulted in the highest grain damage (46.5%), attributed to phenological synchronization with peak weevil oviposition, while late sowing reduced damage by 18.6%. Insecticide application significantly reduced grain damage and increased yield, though the extent of yield improvement depended on sowing time. Overall, seeding rate had minimal influence on yield and pest pressure, although significant variation in grain damage among seeding rates was observed in untreated plots in 2021. Crude protein content (CP) was unaffected by seeding rate but showed inter-annual variation, likely due to environmental conditions. At the optimal sowing time (late April), faba bean yield remained consistently high, and insecticide application had limited impact on yield improvement. Relatively low grain damage under these conditions suggests that insecticide use may be reduced or eliminated. These findings underscore the importance of integrating optimal sowing time with targeted insecticide application to maximize faba bean yield and minimize grain damage in Lithuania.